Characterization and optimization of enzymatic synthesis of kojic acid esters - Mohamad, Rosfarizan (2009)
Kojic acid [5-hydroxy-2-(hydroxymethyl)-1,4-pyrone], is a fungal metabolite produced by many species of fungi Aspergillus oryzae, Acetobacter and Penicillium camembertii. It is used for inhibiting the browning effect of tyrosinase in the food and cosmetic industries. However, kojic acid is water-soluble and its instability has been a problem in cosmetic use. The improvement in oil-solubility of kojic acid through its chemical or lipase-catalyzed acylation with fatty acid has been reported and synthesis of kojic acid ester by chemical method usually results in a complex mixture. Recently, enzymatic synthesis with lipase as catalyst has been used to produce a number of commercially important esters, both by transesterification and by direct esterification. Therefore, an optimized process for high yield enzymatic synthesis of kojic acid ester would benefit manufacturers and be more appealing to consumers. The aims of this research project were set up for better understanding on the relationships between the factors (reaction time, temperature, and enzyme amount and substrate molar ratio) and the response (% molar conversion) of kojic acid esters synthesis, to determine optimal synthesis conditions for kojic acid esters by immobilized lipase using Response surface methodology (RSM) and central composite design (CCD) and to characterize the structure of the product synthesized. RSM and CCD were employed to evaluate the effects of synthesis variables, such as reaction time (24 to 48 h), temperature (30 to 60 0C), enzyme amount (0.1 to 0.4 g) and substrate molar ratio of kojic acid to oleic acid (1:1 to 5:1).The products were extracted and subjected to thin layer chromatography and gas chromatography and the structure of products were confirmed by infra red, gas chromatography-mass spectroscopy and nuclear magnetic resonance. The optimum conditions for the synthesis of kojic acid esters were achieved at 36 h, 45oC, 0.25 g of enzyme amount, mole ratio of 3 (kojic acid/oleic acid), with no added water, no control of water activity and oleic acid as a substrate. By using the optimized condition, the maximum yield of 37% molar conversion, which was compared very well with the maximum predicted value suggested by the RSM, was achieved. An optimised condition for maximum kojic acid esters synthesis was obtained and the product was confirmed via infra red, GCMS and nuclear magnetic resonance analysis. The optimal conditions of kojic acid esters synthesis will be further evaluated using 2L and 100 L stirred tank reactor. An important parameter for the scaling up of kojic acid esters synthesis using a reactor shall be determined and proposed.